HIGHER SCHOOL LOCAL COMPETENCE EDUCATION SPACE AND ITS COMPONENTS - Tatyana A. Lopatukhina; Vladimir G. Zaika; Tatyana V. Zalevskaya (Advanced Engineering Research)
A new type of the higher school education space is considered. The conceptual and terminological framework for its description is presented. The authors’ classification of the student competences developing the integrative phenomenon – competency – is proved.